Factors shaping different trajectories of amphetamine-type-stimulant use: a systematic review of qualitative research. (November 2017) - O'Donnell, Amy; Addison, Michelle; Spencer, Liam; Zurhold, Heike; Rosenkranz, Moritz; McGovern, Ruth; Gilvarry, Eilish; Martens, Marcus-Sebastian; Verthein, Uwe; Kaner, Eileen
Abstract: Background: Amphetamine-type stimulants, including amphetamine, methamphetamine, MDMA, and some novel psychoactive substances, are increasingly popular drugs in the UK and globally. Yet there is limited evidence on what shapes use of amphetamine-type stimulants across the life course. We aimed to systematically review and synthesise recent qualitative literature examining users' perspectives on which factors influence different trajectories of amphetamine-type-stimulant consumption. Methods: We searched MEDLINE, PsycINFO, EMBASE, and ProQuest Social Sciences Premium Collection, between Jan 1, 2000, and Oct 31, 2016, for qualitative research exploring the views of amphetamine-type-stimulant users aged 13 years and older on factors shaping their drug use careers. Only peer-reviewed articles, readily available in the public domain, were retrieved for further review. Two reviewers independently screened potential papers and extracted key data. Thematic synthesis focused on identifying individual, social, and environmental factors relating to initiation, continuation, escalation, and desistance of amphetamine-type-stimulant use. The Critical Appraisal Skills Programme checklist was used to assess methodological quality. Findings: We identified 1694 records, of which 42 papers met our inclusion criteria. 31 studies were rated as being of moderate methodological quality, nine high quality, and two low quality. The literature was internationally diverse, covering North and South America, Europe, Australasia, and southeast Asia. Participants were aged 14–58 years and from varied socioeconomic and demographic groups. Reasons for initiation included: to help manage the transition from opioids; to boost performance at work, college, in sexual relationships, or the home; to promote a sense of social belonging; and to help manage stress. Similar reasons motivated continued use of amphetamine-type stimulants, combined with the challenge of managing withdrawal effects in long-term users. Increased tolerance, experiencing a critical life event, or both contributed to an escalation in use. Reasons for desistance focused on: increased awareness of the negative health impacts of long-term use, particularly during pregnancy; disconnecting from social networks or relationships; and financial instability. Interpretation: To our knowledge, this is the first review of qualitative international literature on amphetamine-type-stimulant use trajectories. The findings underline both the heterogeneous nature of these users, and the diverse social, economic, and individual factors that shape different patterns of use. This information will support the development of more tailored, evidence-based treatment and prevention services in the future. Funding: This report is independent research commissioned and funded by the Department of Health's Policy Research Programme (Grant ATTUNE: Understanding the pathways for stimulant use; ref ST-0416-10001).